CHORD LENGTH DISTRIBUTION FUNCTION FOR A REGULAR HEXAGON - Harutyunyan, H. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2007)
In the paper elementary expression for the chord length distribution function of a regular hexagon is obtained. The formula is derived using σ-formalism in Pleijel identity.